Supernova hemorrhage: obliterative hemorrhage of brain arteriovenous malformations following gamma knife radiosurgery. (13th September 2011) - Alexander, Matthew D; Hetts, Steven W; Young, William L; Halbach, Van V; Dowd, Christopher F; Higashida, Randall T; English, Joey D
Abstract : Hemorrhage represents the most feared complication of cerebral arteriovenous malformations (AVMs) in both untreated patients and those treated with gamma knife radiosurgery. Radiosurgery does not immediately lead to obliteration of the malformation, which often does not occur until years following treatment. Post-obliteration hemorrhage is rare, occurring months to years after radiosurgery, and has been associated with residual or recurrent AVM despite prior apparent nidus elimination. Three cases are reported of delayed intracranial hemorrhage in patients with cerebral AVMs treated with radiosurgery in which no residual AVM was found on catheter angiography at the time of delayed post-treatment hemorrhage. That the pathophysiology of these hemorrhages involves progressive venous outflow occlusion is speculated and the possible mechanistic link to subsequent vascular rupture is discussed.